Fundo constitucional de financiamento do nordeste e desenvolvimento: uma análise do impacto das operações de crédito no crescimento econômico do Maranhão de 2002 até 2017. - MARQUES, João Carlos Souza (2020)
Derived from the relative importance of State into Brazilian development that between many ways is translated into fomentation and subsidized credit to invest, this work based into development theories and the historical process of Brazilian economy, analyzes those subsidy mechanisms active in Northeast, region with the lowest per capita income and greater extremely poverty population and specifically at the Federal Unity with its worse indicators. With focus on the Constitutional Fund for Financing Northeast – FNE managed by the Northeast Bank, which at state level, doesn’t clearly show, impacts on the improvement of income and employment indicators and on development of the most precarious states in which it operates. The purpose of this paper is to investigate the effective contribution of its financing in the development of Maranhão. Constructing a research methodology from the theoretical definitions intersecting with the panel data econometric model in order to verify the relationship between the amount of financing with the employment economic variables, gross value added, formal establishments and wages by large economic sector and the 217 municipalities in the state in which the credit operations were allocated from 2002 to 2017. The econometric model built as Panel Data with Fixed Effects managed to capture that the FNE had positive impacts in terms of Gross Added Value of the Maranhão’s Economy Sectors, of the state GDP and in the amount of formal jobs, however, it was not relevant in the Mass of Income and the number of formal establishments.